Chicken liver and eggshell crackers as a safe and affordable animal source food for overcoming micronutrient deficits during pregnancy and lactation in Indonesia: A double-blind, randomised placebo-controlled trial (SISTIK Growth Study) - Diana, Aly; Rahmannia, Sofa; Suhadi, Yenni Zuhairini; Luftimas, Dimas Erlangga; Rizqi, Haidar; Purnamasari, Afini Dwi; Jihadillah, Ayunda; Ansari, Mohammad Brachim; Haq, Zahrotun; Ayu, Dearly; Pratiwi, Aisyah Nur; Scott, Samuel P.; et al. (Wellcome Trust, 2022)
Background: Indonesia ranks fifth in terms of the number of stunted children and there has been little change in the stunting prevalence in the last decade. In earlier observational studies conducted in 2014-2015, we identified several key underlying problems with the potential to impact stunting in Sumedang district, West Java, Indonesia. Deficits in intakes of growth-limiting micronutrients were observed, most notably calcium, iron, zinc, and vitamin A, emphasizing the need for a food-based intervention to overcome these micronutrient deficits in the diets of mothers and their infants. Methods: A double-blind placebo-controlled cluster randomised trial comparing the effect of daily consumption of 75 grams of locally produced micronutrient-enriched crackers (MEC) (intervention group) compared to placebo crackers (control group) by mothers at two-time intervals: (i) from the 8-14 weeks of pregnancy to delivery (i.e., 28-34 weeks of consumption of MEC) on birth length, and (ii) from the 8-14 weeks of pregnancy to 5 months post-partum on attained linear growth and linear growth velocity of breast-fed infants. A total of 324 pregnant women from 28 clusters (villages) located in 3 sub-districts in Sumedang district, West Java, Indonesia, will be randomly assigned to either intervention (n=14 villages) or control (n=14 villages). Discussion: This will be the first study in Indonesia to use crackers based on powdered eggshells and chicken liver, in a form which is acceptable, safe, and has a long shelf life. If daily consumption of MEC for 6 months during pregnancy can enhance birth length, or their continued daily consumption for 5 months postpartum improves both attained and incremental linear growth at 5 months of age, then scaling-up in Indonesia may be considered.